2022
DOI: 10.1186/s12909-022-03493-6
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study for the development and validation of a reflective inventory to quantify diagnostic reasoning skills in optometry practice

Abstract: Background Diagnostic reasoning is an essential skill for optometry practice and a vital part of the curriculum for optometry trainees but there is limited understanding of how diagnostic reasoning is performed in optometry or how this skill is best developed. A validated and reliable self-reflective inventory for diagnostic reasoning in optometry, would enable trainees and registered practitioners to benchmark their diagnostic reasoning skills, identify areas of strength and areas for improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 26 publications
2
13
1
Order By: Relevance
“…Student experiences were evaluated as part of a quality assurance activity using a voluntary and anonymous survey instrument at the completion of the fifth week. Pre-existing scores from the Diagnostic Thinking Inventory for Optometry (DTI-O) before and after the learning activity were included in the study [ 7 ]. After the 5 th week, all students and facilitators were invited to participate in focus group discussions with two to four students or two to four facilitators.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Student experiences were evaluated as part of a quality assurance activity using a voluntary and anonymous survey instrument at the completion of the fifth week. Pre-existing scores from the Diagnostic Thinking Inventory for Optometry (DTI-O) before and after the learning activity were included in the study [ 7 ]. After the 5 th week, all students and facilitators were invited to participate in focus group discussions with two to four students or two to four facilitators.…”
Section: Methodsmentioning
confidence: 99%
“…The inventory has two subdomains, 21 items for Flexibility in Thinking (FT) and 20 items for Structured Memory (SM). Flexibility in thinking focuses on the skill of moving between different enquiry processes and structured memory relates to the ability to process possessed knowledge to solve clinical cases [ 7 ]. A higher score on the DTI-O represents greater diagnostic reasoning skills with a maximum score of 246 (126 in FT and 120 in SM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DTI is a reliable tool for determining the level of FT and SM that experts and medical students use in clinical reasoning processes [ 1 , 7 , 12 ], it consists of 41 overlapping items that can be inconvenient to use. Edgar et al [ 7 ] recently adapted DTI for use in optometric education contexts through context-based changes. They created a shorter version of the DTI in optometric education contexts (DTI-OS) by reducing items from the original DTI.…”
Section: Introductionmentioning
confidence: 99%
“…The DTI-OS in their study demonstrated a high level of internal reliability, with a Cronbach’s α of 0.92, and its validity was established with significantly higher scores by qualified optometrists compared to second-year optometry students. Edgar et al [ 7 ] also measured the clinical reasoning abilities of second-year optometry students using the original DTI. Despite the different contexts, its mean value (155.6) of second-year optometry students in their study was comparable to the mean value (158.3) of third-year medical students in Bordage et al [ 1 ].…”
Section: Introductionmentioning
confidence: 99%